Dampak Covid-19 terhadap Sektor Industri - Jodi Wahyudi; Desiyana (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this study is to find out what Rhenaldi Kasali's perception is in the change house's YouTube channel entitled